The Relationship Between Brand Evidence and Brand Hearsay Towards Brand Verdicts in Service - Nur Elyani, Hasan (2009)
Nowadays, service branding is seen as an important part which helps the service organization brand their service. There are some elements in service branding that the organization must have in order to retain the consumer’s re-patronage intention to the service offered. This study examined the relationship between brand evidence and brand hearsay towards brand verdicts in service. There are three objectives were determined in the study. For about 294 respondents which consist of 201 trainee teachers of Kursus Perguruan Lepasan Ijazah (KPLI) program and 93 lecturers from Institut Pendidikan Guru Malaysia, Perlis Campus were involved in the study, representing a response rate of 81.89 percent of the total questionnaires distributed. Hypotheses testing method were employed, and self-administered questionnaire with five-point Likert scale was used to collect the data. Data were analyzed through Pearson correlation and multiple regressions analysis. The findings found out that there is positive relationship between brand evidence and brand hearsay towards brand verdicts in service, thus accepted the hypotheses. Regression analysis revealed that brand evidence influenced brand verdicts greater than brand hearsay, by explaining 47.6 percent of the brand verdicts variance.Implication of the findings, limitation of the study and recommendation for future research were offered.